The Transformation of Tribal Fanaticism: An Analysis of the Prophet’s Hadith Response to the Practice of ‘Ashabiyah in the Jahiliyyah Era - Edi Massolihin; M Iqbal as-shidqi; Mohd fadli; Hamzah fauriz (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2025)
Tribal fanaticism or ashabiyah is a fundamental problem that has taken root in the social order of Arab society during the Jahiliyyah era. This phenomenon not only created division, but also gave rise to various forms of detrimental social discrimination. In addressing this issue, Islam emerged by offering transformative solutions through the hadiths of the Prophet Muhammad (PBUH). This study has several main objectives. First, to analyze in depth how the patterns of tribal fanaticism were formed within the social structure of pre-Islamic Arab society, as well as the impacts it produced. Second, to examine the responses and transformative approaches contained in the prophetic hadiths in overcoming this issue. Third, to identify various challenges in the effort to contextualize these hadiths within contemporary realities. The methodology applied in this study is library research, which involves collecting data from various comprehensive literature sources. These sources include hadith commentaries, reference books, scientific journals, academic articles, and various other written sources relevant to the research topic. The material object that becomes the focus of the study is the hadiths that specifically discuss tribal fanaticism. (Involvement & Conclusions): This research involves an in-depth examination of classical and contemporary literature on ashabiyah, including textual and contextual analyses of the related hadiths. Through this approach, it is found that Islam offers a fundamental transformation from tribal fanaticism toward universal brotherhood based on faith (ukhuwah Islamiyah). The prophetic hadiths not only criticize the practice of ashabiyah, but also provide ethical and social foundations for building a more inclusive and just society. This study contributes to expanding the understanding of Islamic solutions to tribal fanaticism and its relevance to contemporary social challenges.